Interdiffusion and intereaction of steel-composite-sialon joint / Patthi Hussain and Othman Mamat (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
The reason for introducing a composite as an interlayer is because it can improve the fracture toughness of the sialon and also give an intermediate coefficient of expansion between sialon and steel. Hence during cooling down of the joining process the residual stress is reduced. Initially, a composite of 80V% sialon and 20V% 316 austenitic stainless steel was prepared through the powder metallurgy technique. The composite was joined to the sialon at 1550°C for 1 hour under a pressure of 15 bar. It was then joined to 316L austenitic stainless steel at 1250° C for 1 hour under the same pressure. Optical micrograph revealed that a good interface was formed between the composite and the sialon. It also revealed a good interface between the austenitic stainless steel and the composite. Investigation on the mechanical property of the joint was performed across the interfaces of metal, composite and ceramic using hardness measurement. Scanning Electron Micrograph (SEM) analyses with Energy Dispersive Spectrometer (EDS) revealed the interdiffusion and intereaction of the steel-composite-sialon joint. As a conclusion, a good reaction between the sialon and the composite and between the composite and the steel were achieved.